Analisis Kehalalan Produk Pembersih Wajah Berdasarkan Kandungan Etanol Menggunakan Metode Kromatografi Gas - Azzahra, Maharani Fathiya; Nofita, Nofita; Tutik, Tutik (Jurnal Ilmiah Wahana Pendidikan, 2024)
The usage of cosmetic product especially facial cleanser has become a routine activity for Indonesian societies who are muslim in majority. Ethanol is one of the materials in producion of facial cleanser product that need to be known the percentage of its rate in a product so that it is halal and safe to be used by all the muslims in Indonesia. This research was conducted by testing samples of facial cleansers circulatin at Center of Tanjung Karang Subdistrict market, Bandar Lampung City qualitatively and quantitatively. Qualitative testing of the samples resulted in indications of ethanol content in 6 out of 10 samples as indicated by the color change of the sample to brown and the presence of precipitate when it was dripped by NaOH and CuSO4 solution. Qualitative tests were carried out on 6 samples that indicated they contained ethanol using a gas chromatograph equipped with a flame ionization detector (GC-FID) at the LPPOM MUI Laboratory. The six samples, namely sample A had an ethanol content of 86.96%, sample B had an ethanol content of 62.36%, sample C had an ethanol content of 0.44%, sample D had an ethanol content of 3.21%, sample E had a concentration of 2.00%, and sample F had a concentration of 0.88%. 8 out of 10 samples fulfill the requirements for the ethanol content limit in a cosmetic product based on MUI Fatwa No. 40 of 2018 and BPOM Regulation No. 17 of 2022, namely samples C, D, E, F, G, H, I, and J, while 2 samples did not fulfill the requirements, namely samples A and B